PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS VI UPTD SDN 212 INPRES PANGKAJENE KECAMATAN MAROS BARU KABUPATEN MAROS - wahyuni, silvi; Kaddas, Badruddin; Musbaing , Musbaing (ALENA : Journal of Elementary Education, 2023)
The purpose of this study was to investigate whether Islamic Religious Education has an influence on student character and the extent to which this influence occurs in class VI students of UPTD SDN 212 Inpres Pangkajene. This research uses a quantitative approach with a correlation method. The data sources used consisted of primary data obtained through questionnaires and secondary data obtained from books and articles. Data collection techniques involved observation, questionnaires, and documentation. The population in this study consisted of 22 respondents, and the entire population was sampled using the total sampling technique. Data analysis was conducted through simple regression analysis, with Islamic Religious Education as the independent variable, and character as the dependent variable. Based on the research results, hypothesis testing shows that Islamic Religious Education has a t value of 3.313, with a significance level of 0.003. In this case, t count (3.313) is greater than t table (2.0859), and the significance level (0.003) is smaller than 0.05. This shows that the hypothesis in this study rejects the null (Ho) and accepts the alternative (Ha), which means that there is a significant influence between Islamic Religious Education and the character of students. Through the calculations carried out, a linear regression equation Y = 29.439 + 0.252X was obtained, with a significance level (sig.) of 0.003, which is less than 0.05 (alpha). Thus, it can be concluded that there is an influence between Islamic Religious Education and character. Based on the R2 (R Square) value obtained of 0.047 (0.217 x 0.217) or 4.7%, it can be concluded that Islamic Religious Education has a significant influence on the character of grade VI UPTD SDN 212 Inpres Pangkajene students.